Parents’ and caregivers’ role toward childhood vaccination in Albania: assessment of predictors of vaccine hesitancy - Gjini, E.; Moramarco, S.; Carestia, M. C.; Cenko, F.; Ylli, A.; Mehmeti, I.; Palombi, L.; Buonomo, E. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Vaccination has saved millions of lives through the protection of individuals and populations from communicable diseases. Vaccine hesitancy, defined as the delay in acceptance or refusal of vaccines despite the availability of vaccination services, has become a growing global concern. The objective of this study was to investigate parents’/caregivers’ hesitancy toward childhood vaccination and its predictors in Albania.Study design. A cross-sectional survey was conducted.Methods. The data comes from a survey conducted on a sample of parents/caregivers (89.6% mothers) of children aged 6 months to 8 years at health care vaccination centers in seven Albanian cities from December 2020 to February 2021. Parents/caregivers (one per child) were interviewed by trained healthcare staff using a standardized questionnaire on six main content domains, including immunization behavior, beliefs about vaccine safety and efficacy, attitudes about vaccines, vaccination confidence, estimation of vaccine delay, and the intention to immunize children against SARS-CoV-2, and a self-reported hesitancy. The Albanian Ministry of Health approved the questionnaire, after it was translated, validated and adapted to the local setting. Statistical analyses included independent sample t-tests (p